'Wo benanε a εyε bebree': The economic impact of remittances of Netherlands-based Ghanaian migrants on rural Ashanti - Kabki, M.; Mazzucato, V.; Appiah, E. (Population, Space and Place, 2004)
This paper explores the ways remittances from Netherlands-based Ghanaian migrants influence economic and social life in rural areas in the Ashanti region in Ghana, both at family and village levels. The analysis focuses on eight domains of economic life, selected for their importance within Ashanti culture. They are: investments in housing, business, farm, education, and community development projects, health care, and participation in church and funerals. The findings are based on 60 interviews with village leaders and families of migrants in 25 Ashanti villages collected between December 2002 and January 2003. The paper argues that most Netherlands-based migrants invest in housing and business back home, but also support their families with contributions towards education, healthcare and daily upkeep. Apart from direct support to families, groups of migrants have contributed towards various development projects. The indirect impact of migration on community development is also manifested in individual migrant-financed activities that provide needed services to the communities. However, this impact varies between families and between communities, due to a number of external factors that influence the volume and frequency of remittances to families and the ability of home communities to benefit from migrant-financed support. The paper argues that remittances can contribute greatly to the well-being and development of a family, but at the same time these can be highly insecure sources of income because the family may fall back into poverty the moment the flow of money from abroad stops. © 2004 John Wiley & Sons, Ltd.
Keywords: Culture; Development; Economy; Ghana; Migration; Remittances; Rural Ashanti; The Netherlands